Banking union: the problem of untried systems. Issue 3 (3rd July 2018) - Mayes, David G.
Abstract : This article explores the problems the EU and the SRB face in trying to implement a credible system for resolving banks without the use of taxpayer funds as a key part of banking union that avoids the doom loop between indebted banks and indebted sovereigns. It finds that without clear examples of how the system works in practice it is very difficult to provide convincing evidence of what will happen given the large number of options for bailing in, the continuing predilection for bailing out in some states and the lack of fiscal backstop for general threats to financial stability.